2008
DOI: 10.1094/phyto-98-11-1233
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Efficiency of Cucumber mosaic virus by Aphids Associated with Virus Epidemics in Snap Bean

Abstract: Cucumber mosaic virus (CMV) is a major component of the virus complex that has become more pronounced in snap bean in the midwestern and northeastern United States since 2001. Multiple-vector-transfer tests were done to estimate the CMV transmission efficiencies (p) of the main aphid species identified in commercial snap bean fields in New York and Pennsylvania. The four most efficient vectors (p > 0.05) were Aphis gossypii, A. glycines, Acyrthosiphon pisum, and Therioaphis trifolii, which were all significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 29 publications
2
59
0
Order By: Relevance
“…To facilitate the comparison, the transmission rate for a single aphid (P * ) was calculated from our data and from data of previous studies (Table 3). The transmission efficiency of CmV by A. pisum red morph was higher than for green morph in this study, which was similar to the results obtained previously for this virus by Aphis gossypii (Pinto et al, 2008;Gildow et al, 2008;Garzo et al, 2004). on the other hand, the transmission efficiency for single green morph of A. pisum in this study was determined as 0.01-0.03, similar to the results of Gildow et al (2008) on A. pisum and Aphis craccivora transmission efficiency for CmV-le isolate on P. vulgaris.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…To facilitate the comparison, the transmission rate for a single aphid (P * ) was calculated from our data and from data of previous studies (Table 3). The transmission efficiency of CmV by A. pisum red morph was higher than for green morph in this study, which was similar to the results obtained previously for this virus by Aphis gossypii (Pinto et al, 2008;Gildow et al, 2008;Garzo et al, 2004). on the other hand, the transmission efficiency for single green morph of A. pisum in this study was determined as 0.01-0.03, similar to the results of Gildow et al (2008) on A. pisum and Aphis craccivora transmission efficiency for CmV-le isolate on P. vulgaris.…”
Section: Discussionsupporting
confidence: 92%
“…results revealed that geographical isolates of CmV, which were isolated from bean and cowpea, were transmissible by pea aphid, similar to results of Gildow et al (2008), who reported a successful transmission of CmV to snap bean plants by A. pisum. our results showed that red morph of A. pisum is a more efficient vector of CmV than green morph in greenhouse condition.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In this research plants evaluated after 21 days based on some researches [33] despite showing difference in morphological parameters including top fresh/dry weights and plant height between control and treated plants, yet for most lines there was non statistical significant difference (Table 3). It is concluded that plants should checked after longer growth period as suggested by other researchers [5,12]. This investigation showed that line D81083 had moderate resistance to CMV and the virus was not detected in it by ELISA, while the virus can replicate in this line with low titer.…”
Section: Discussionmentioning
confidence: 61%
“…CMV is aphid transmitted in a stylet-borne non-persistent manner [12] and is seed borne in some hosts [38,40]. CMV seed transmission in susceptible bean cultivars is up to 49 % [7] and is retained in the seed for about 27 months during storage [3].…”
Section: Introductionmentioning
confidence: 99%